First-principles investigation of mechanical properties, elastic anisotropy, and ultralow lattice thermal conductivities of ductile Mg–Bi alloys. (December 2022) - Chen, Yingying; Zuo, Enci; Dou, Xilong; Chen, Li; Jiang, Gang; Mao, Aijie
Abstract: The crystal structures, mechanical properties, anisotropic properties, and lattice thermal conductivities of Mg–Bi alloys have been investigated by particle swarm optimization structure prediction method and first-principles calculations. Apart from the well-known stoichiometry of Mg3 Bi2, the novel stable stoichiometry of Mg4 Bi, as well as several metastable stoichiometries (i.e., Mg3 Bi, Mg2 Bi, and MgBi) are predicted. Meanwhile, the calculated phonon dispersion curves and elastic constants show that the above five Mg–Bi alloys are dynamically and mechanically stable, respectively. Moreover, the calculated mechanical properties indicate that the studied Mg–Bi alloys with various stoichiometries behave ductility. Simultaneously, they exhibit obvious anisotropic characters and the degree of anisotropy follows the order of MgBi > Mg2 Bi > Mg3 Bi > Mg4 Bi > Mg3 Bi2 . More importantly, the minimum lattice thermal conductivities of MgBi and Mg2 Bi are smaller than that of the well-known Mg3 Bi2 . The adsorption of O atom on the Mg3 Bi (001) surface is more sensitive compared with other four Mg–Bi (001) surfaces. Highlights: Apart from the well-known stoichiometry of Mg3 Bi2, the novel stable stoichiometry of Mg4 Bi, as well as several metastable stoichiometries (i.e., Mg3 Bi, Mg2 Bi, and MgBi) are predicted. The five Mg–Bi alloys are dynamically and mechanically stable. The five Mg–Bi alloys behave ductility and obvious anisotropy. The minimum lattice thermal conductivities of MgBi and Mg2 Bi are smaller than that of Mg3 Bi2 .